Information Disclosed in Patent Documents being the Source to Address Emergencies: A Strategy to Achieve Technological Developments Addressing COVID-19 - Martins, Tatiana D; Cordeiro, Diéricon S (Recent patents on biotechnology, 2021)
Face COVID-19 pandemic, a need for accurate information on SARS-CoV-2 virus is urgent and scientific reports have been published on a daily basis to enable effective technologies to fight the disease progression. However, at the initial occurrence of Pandemic, no information on the matter was known and technologies to fight the Pandemic were not readily available. However, searches in patent databases, if strategically designed, can offer quick responses to new pandemics.BACKGROUNDFace COVID-19 pandemic, a need for accurate information on SARS-CoV-2 virus is urgent and scientific reports have been published on a daily basis to enable effective technologies to fight the disease progression. However, at the initial occurrence of Pandemic, no information on the matter was known and technologies to fight the Pandemic were not readily available. However, searches in patent databases, if strategically designed, can offer quick responses to new pandemics.The objective of this study is aiming to provide existing information in patent documents useful for the developmentof technologies addressing COVID-19. Considering the emergency situation the world was facing and the knowledge of COVID-19 available until April, 2020, this work presents an analysis of the main characteristics of the technological information in patent documents worldwide, related to coronaviruses and the severe acute respiratory syndrome (SARS).OBJECTIVEThe objective of this study is aiming to provide existing information in patent documents useful for the developmentof technologies addressing COVID-19. Considering the emergency situation the world was facing and the knowledge of COVID-19 available until April, 2020, this work presents an analysis of the main characteristics of the technological information in patent documents worldwide, related to coronaviruses and the severe acute respiratory syndrome (SARS).Regions of concentration of such technologies, the number of available documents and their technological fields are disclosed in three approaches: 1) a wide search, retrieving technologies on SARS or coronaviruses; 2) a targeted search, retrieving documents additionally referring to Angiotensin converting enzyme (ACE2), which is used by SARS- CoV-2 to enter a cell and 3) a punctual search, which retrieved patents disclosing aspects related to SARS- CoV-2 available at that time.METHODSRegions of concentration of such technologies, the number of available documents and their technological fields are disclosed in three approaches: 1) a wide search, retrieving technologies on SARS or coronaviruses; 2) a targeted search, retrieving documents additionally referring to Angiotensin converting enzyme (ACE2), which is used by SARS- CoV-2 to enter a cell and 3) a punctual search, which retrieved patents disclosing aspects related to SARS- CoV-2 available at that time.Results show the high-level technology involved in these developments and a monopoly tendency of such technologies, also evidencing that it is possible to find answers to new problems in patent documents.RESULTSResults show the high-level technology involved in these developments and a monopoly tendency of such technologies, also evidencing that it is possible to find answers to new problems in patent documents.This work, then, aims to contribute to scientific and technological development by raising the awareness of what should be considered when searching for technologies developed for other matters that could provide solutions for a new problem.CONCLUSIONThis work, then, aims to contribute to scientific and technological development by raising the awareness of what should be considered when searching for technologies developed for other matters that could provide solutions for a new problem.